The Effect of Master Model To Students Understanding of Mathematical Concepts - Cania Kastira; Irwan Irwan (International Journal of Multidisciplinary Research of Higher Education, 2023)
Understanding of mathematical concepts is one of the abilities that must be possessed by students, because it’s the basic to achieve the aims of further mathematics learning. However, the fact is that the understanding of mathematical concepts of grade 8 students of Junior High School 1 2x11 Enam Lingkung is still low, so it needs to be improved. The learning is still teacher-centered in the classroom with the result that the students were not able to construct their knowledge. One of the learning models that can support students to actively construct their knowledge is MASTER learning model. This kind of research is both descriptive and quasi experiment, with Static Group Design. Based on the results of data analysis it can be concluded as follows: the first is the activites of students who learn with MASTER learning model is better than those who learn with conventional learning. The second is obtained P- values = 0.024 < α = 0.05, so that understanding the mathematical concepts of students who learn with MASTER learning model is better than those who learn with conventional learning.